Immigration and crime: taking stock - Kubrin, Charis Elizabeth (SpringerBriefs in criminology, 2023)
This brief examines various dimensions of the immigration-crime relationship in the United States. It evaluates a range of theories and arguments asserting an immigration-crime link, reviews studies examining its nature and predictors, and considers the impacts of immigration policy. Synthesizing a diverse body of scholarship across many disciplinary fields, this brief is a comprehensive resource for researchers engaged in questions of linkages between crime and immigration, citizenship, and race/ethnicity, and for those seeking to separate fact from fiction on an issue of great scientific and social importance.